Some Factors for Growing Savings to Be Well-Thought-Out by Key Actors in Kosovo (European Journal of Marketing and Economics, 2024)
A primary impediment to sustainable macroeconomic development in developing nations is the persistent lack of domestic investment, which consequently limits a country's long-term economic growth potential. Developing the real sector of an economy is a critical challenge that cannot be left to random market actors; therefore, the Government of Kosovo, the Central Bank of Kosovo, and local commercial banks represent the three primary institutional pillars that must strategically focus on factors influencing the growth of domestic savings. By systematically channeling these savings back into the Kosovar economy through banking channels for investments in healthy financial capital, Kosovo can become economically and politically more developed and self-reliant. Based on extensive literature analysis and empirical data processing, this paper identifies the core systemic factors that can effectively stimulate savings growth in Kosovo, thereby expanding the financial capital available to local entrepreneurs and ensuring the continuity of the country's economic expansion. The research isolates and analyzes key drivers of increased saving behavior, including taxation and disposable income levels, demographic variables, public confidence and deposit security, the physical banking network, the potential role of a state-owned bank, financial education, and broader financial inclusion. While the prevailing interest rate is universally recognized as another important factor, this study intentionally omits it from the core framework, as it is frequently the standalone subject of other specialized literature, allowing this paper to provide a deeper, multi-dimensional analysis of the institutional and socio-economic determinants of capital accumulation.
Keywords: commercial banks, savings, factors for growing savings